Project Based Learning Implementation On Teaching Writing Descriptive Text About Athletes To 10th Grade Students At SMKS-1 Tamansiswa - Gian Reynaldo Pandiangan; Bintoro Manalu; Naomi Simanjuntak; Sanju Febrio Saragih; Dumaris E. Silalahi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2026)
This research explores the integration of Project-Based Learning (PjBL) as a pedagogical approach for enhancing descriptive writing skills about athletes among Grade X students at SMKS-1 Tamansiswa. Utilizing a descriptive qualitative methodology through a case research framework, data were gathered via classroom observations, semi-structured interviews, and the analysis of students’ written compositions. The results demonstrate that PjBL was executed in a well-organized manner, following clearly defined project stages that fostered a student-centered learning environment. Students demonstrated active engagement in research and writing processes, which contributed significantly to their development in essential writing components such as content, vocabulary, grammar, and organization. The choice of authentic, interest-based topics served to boost motivation and participation, while effective teacher facilitation and peer feedback further supported students’ writing progress. Despite encountering some challenges related to information accessibility, the overall outcomes indicate a positive impact on students’ descriptive writing abilities. This research concludes that PjBL serves as a highly effective teaching strategy for cultivating descriptive writing skills within EFL vocational education settings.